Negative Connotations of the “Russian World” Concept against the Backdrop of the Russian-Ukrainian War 2022 - Starodubtseva, Anastassiya (Respectus Philologicus, 2022)
For a long time, the idea of the so-called “Russian world”, a civilization united according to linguistic, ethnocultural, and religious principles, has been the subject of numerous interdisciplinary studies. It is primarily due to the aggravation of the geopolitical situation in the sphere of Russian influence, such as Ukraine. Existing studies are devoted to historical, cultural, and philosophical aspects. However, there are still not enough linguistic ones since there is still no single definition of the essence of this phenomenon and the features of its functioning in various discourses. Today, in the scientific space, there are three main theoretical approaches to understanding the “Russian world” – civilizational, geopolitical, and religious. In this study, the task is to conceptualize the presented “Russian world” notion as well as to identify newly developed connotations in connection with the Russian-Ukrainian military conflict of 2022, utilizing semantic analysis, component, and contextual analysis methods. The media texts of the Russian-language Ukrainian media were used as the material of the study, reflecting the military conflict between Russia and Ukraine and mentioning the “Russian world” concept. The study showed that the “Russian world” concept had acquired numerous negative connotations, such as “war, destruction, death”.